Report Of The University of Minnesota Commission On Campus Demonstrations - Minnesota Univ., Minneapolis; Minnesota Univ., Minneapolis ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
A commission of 23 faculty members, students, and an alumnus was appointed to study problems arising from student demonstrations at the University of Minnesota in the fall of 1967, and to recommend policies by which the university could deal with such problems. The commission, appointed by the university's president, was to formulate guidelines by which the university could distinguish between peaceful or legitimate, and violent or disruptive, demonstrations. The 16 guidelines presented in the report are largely based on existing procedures for the enforcement of university policy on demonstrations by punitive actions when all other means have failed. The commission permits and encourages the use of university grounds as a forum for the free exchange and criticism of ideas, but it emphasizes the need for students, teachers, administrators, and other members of the university community to follow orderly demonstration procedures that do not disrupt instructional, administrative, or other functions of the university. The guidelines also discuss distinctions between different types of demonstrations, who should identify, arrest and remove trespassers from the campus, off-campus student activities, the use of the university's name, and institutional supervision and control over individual or group misconduct. (WM)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Administration; Extracurricular Activities; Activism; Administrative Policy; Demonstrations (Civil); Higher Education; Student Participation